Daytime Oxidized Reactive Nitrogen Partitioning in Western U.S. Wildfire Smoke Plumes. Issue 4 (16th February 2021) - Juncosa Calahorrano, Julieta F.; Lindaas, Jakob; O'Dell, Katelyn; Palm, Brett B.; Peng, Qiaoyun; Flocke, Frank; Pollack, Ilana B.; Garofalo, Lauren A.; Farmer, Delphine K.; Pierce, Jeffrey R.; Collett, Jeffrey L.; Weinheimer, Andrew; et al.
Abstract: The Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen (WE‐CAN) deployed the NSF/NCAR C‐130 aircraft in summer 2018 across the western U.S. to sample wildfire smoke during its first days of atmospheric evolution. We present a summary of a subset of reactive oxidized nitrogen species (NOy ) in plumes sampled in a pseudo‐Lagrangian fashion. Emissions of nitrogen oxides (NOx  = NO + NO2 ) and nitrous acid (HONO) are rapidly converted to more oxidized forms. Within 4 h, ∼86% of the ΣNOy is in the form of peroxy acyl nitrates (PANs) (∼37%), particulate nitrate ( p NO3 ) (∼27%), and gas‐phase organic nitrates (Org N(g) ) (∼23%). The average e ‐folding time and distance for NOx are ∼90 min and ∼40 km, respectively. Nearly no enhancements in nitric acid (HNO3 ) were observed in plumes sampled in a pseudo‐Lagrangian fashion, implying HNO3 ‐limited ammonium nitrate (NH4 NO3 ) formation, with one notable exception that we highlight as a case study. We also summarize the observed partitioning of NOy in all the smoke samples intercepted during WE‐CAN. In smoke samples intercepted above 3 km above sea level (ASL), the contributions of PANs and p NO3 to ΣNOy increase with altitude. WE‐CAN also sampled smoke from multiple fires mixed with anthropogenic emissions over the California Central Valley. We distinguish samples where anthropogenic NOx emissions appear to lead to an increase in NOx abundances by a factor of four and contribute to additional PAN formation. Key Points: NOx and HONO are rapidly converted to other species. The average e‐ folding time (distance) for NOx is ∼90 min (∼40 km) In 4 h, PANs contribute ∼37% of the ΣNOy species in smoke; p NO3 is the second largest (∼27%) contributor In 4 h, Org N(g) constitute a large portion (∼23%) of the ΣNOy in the plumes sample during WE‐CAN